Femtosecond X-ray diffraction: Experiments and limits - Wark, J; Allen, A; Ansbro, P; Bucksbaum, P; Chang, Z; DeCamp, M; Falcone, R; Heimann, P; Johnson, S; Kang, I; Kapteyn, H; Larsson, J; et al. (2001)
Although the realisation of femtosecond X-ray free electron laser (FEL) X-ray pulses is still some time away, X-ray diffraction experiments within the sub-picosecond domain are already being performed using both synchrotron and laser-plasma based X-ray sources. Within this paper we summarise the current status of some of these experiments which, to date, have mainly concentrated on observing non-thermal melt and coherent phonons in laser-irradiated semiconductors. Furthermore, with the advent of FEL sources, X-ray pulse lengths may soon be sufficiently short that the finite response time of monochromators may themselves place fundamental limits on achievable temporal resolution. A brief review of time-dependent X-ray diffraction relevant to such effects is presented.